Úvod do kvantových svazů - Šlesinger, Radek, 1984-; Paseka, Jan, 1962-; Masarykova univerzita. Přírodovědecká fakulta. Katedra matematiky (2006)
The thesis aims to provide a basic survey of the theory of quantales and quantale modules. The first chapter introduces quantales, gives examples of them, and presents basic constructions in the category of quantales, finishing with projective and injective objects. The second chapter provides a similar overview of modules over quantales.
Vedoucí práce: Jan Paseka.
Bakalářská práce (Bc.)--Masarykova univerzita, Přírodovědecká fakulta, 2006.
Keywords: svazy (algebra); lattices (algebra); bakalářské práce